The Effect of Depression, Stigma, and Peer Support Group, on the Quality of Life of People Living with HIV/AIDS in Solo Plus Peer Support Group, Surakarta, Central Java - Yuli Lutfatul Fajriyah; Argyo Demartoto; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: People Living with HIV/AIDS (PLWH) often face tough social problems, such as social rejection, stigma, and discrimination. Factors that affect PLWH’s quality of life may include psychosocial factors, economic status, immunological status, social support, and co-morbidity. This study aimed to determine the effect of depression, stigma, and peer support group on the quality of life of people living with HIV/AIDS in Solo Plus peer support group, Surakarta, Central Java.Subjects and Method: This was an analytic observational study with a cross-sectional design. The study was conducted at Solo plus peer support group, Surakarta, Central Java, from January to February 2018. A sample of 100 PLWH was selected for this study by simple random sampling. The dependent variable was a quality life of PLWH. The independent variables were healthy behavior, depression, family income, stigma, peer support, and social support. The data were collected by questionnaire and analyzed by path analysis.Results: Quality of life of PLWH increased with involvement in peer support group (b= 3.40; 95% CI= 0.71 to 6.10; p=0.001), social support (b= 0.70; 95% CI= 0.01 to 1.40; p=0.046), and healthy behavior (b=9.33; 95% CI= 5.30 to 13.36; p<0.001). Quality of life of PLWH decreased with stigma (b= -1.10; 95% CI=-1.84 to -0.36; p=0.003), and depression (b=-4.23; 95% CI=-6.62 to -1.83; p=0.001). Quality of life of PLWH was indirectly affected by income (b=0.06; 95% CI=10.14 to 18.61; p<0.001).Conclusion: Quality of life of PLWH is affected by healthy behavior, depression, stigma, peer support group, social support, and income.Keywords: Quality of life, PLWH, stigma, peer support group, social support Correspondence: Yuli Lutfatul Fajriyah. Masters Program in Public Health, Sebelas Maret University, Surakarta, Jl. Ir. Sutami No. 36 A, 57126, Surakarta, Central Java. Email: yuli.luth.15@gmail.com. Mobile: +6285712200298.Journal of Health Promotion and Behavior (2018), 3(1): 27-36https://doi.org/10.26911/thejhpb.2018.03.01.03